2007
DOI: 10.1136/bmj.39345.405243.be
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of antibiotics against serious complications of common respiratory tract infections: retrospective cohort study with the UK General Practice Research Database

Abstract: Objective To determine the extent to which antibiotics reduce the risk of serious complications after common respiratory tract infections. Design Retrospective cohort study. Setting UK primary care practices contributing to the general practice research database. Data source 3.36 million episodes of respiratory tract infection. Main outcome measures Risk of serious complications in treated and untreated patients in the month after diagnosis: mastoiditis after otitis media, quinsy after sore throat, and pneumon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
218
2
8

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(235 citation statements)
references
References 21 publications
7
218
2
8
Order By: Relevance
“…A cute sore throat is one of the most common symptoms among patients presenting to primary care. 1,2 Sore throats resulted in 92 million estimated visits by adults to primary care practices and emergency departments in the United States between 1997 and 2010, averaging 6.6 million annually; with unnecessary antibiotic prescribing costs of at least $500 million. 3 Antibiotics are prescribed at 60% of UK primary care sore throat consultations, 4 and the trend is not decreasing 3,5 despite the low risks of suppurative complications, limited symptomatic benefit, 6 and national guidelines advising against prescriptions.…”
Section: Resultsmentioning
confidence: 99%
“…A cute sore throat is one of the most common symptoms among patients presenting to primary care. 1,2 Sore throats resulted in 92 million estimated visits by adults to primary care practices and emergency departments in the United States between 1997 and 2010, averaging 6.6 million annually; with unnecessary antibiotic prescribing costs of at least $500 million. 3 Antibiotics are prescribed at 60% of UK primary care sore throat consultations, 4 and the trend is not decreasing 3,5 despite the low risks of suppurative complications, limited symptomatic benefit, 6 and national guidelines advising against prescriptions.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence from clinical trials suggests that antibiotics may reduce the risk of suppurative complications of RTIs,5 but the more serious complications are generally too rare to evaluate precisely in randomised studies. A cohort study in 162 general practices in the General Practice Research Database from 1991 to 2001 evaluated the effect of antibiotic treatment on the incidence of pneumonia after upper RTI, peritonsillar abscess after sore throat, and mastoiditis after otitis media 14. The results suggested that antibiotic treatment was associated with lower odds of each of these complications, but the overall risk of complications was generally small and the number of patients who would have to be treated to avoid one complication was estimated to be in excess of 4000.…”
Section: Introductionmentioning
confidence: 99%
“…Selection bias is a potentially important issue among low recruiting doctors, but the study found no evidence of clinical differences comparing higher and lower recruiting doctors. Overall fewer children than expected from historical data sets 27 were recruited which probably reflects reluctance of parents and/or GPs to expose children to a throat swab, but since the study elected not to include age per se in the model, the impact of this should be slight.…”
Section: Strengths and Limitationsmentioning
confidence: 99%